Cobalt(II) Oxidation by the Marine Manganese(II)-Oxidizing Bacillus sp. Strain SG-1 - Lee, Yoon (1994)
The geochemical cycling of cobalt (Co) has often been considered to be controlled by the scavenging and oxidation of Co(II) on the surface of manganese [Mn(III,IV)] oxides or manganates. Because Mn(II) oxidation in the environment is often catalyzed by bacteria, we have investigated the ability of Mn(II)-oxidizing bacteria to bind and oxidize Co(II) in the absence of Mn(II) to determine whether some Mn(II)-oxidizing bacteria also oxidize Co(II) independently of Mn oxidation. We used the marine Bacillus sp. strain SG-1, which produces mature spores that oxidize Mn(II), apparently due to a protein in their spore coats (R.A. Rosson and K. H. Nealson, J. Bacteriol. 151:1027-1034, 1982; J. P. M. de Vrind et al., Appl. Environ. Microbiol. 52:1096-1100, 1986). A method to measure Co(II) oxidation using radioactive (57)Co as a tracer and treatments with nonradioactive (cold) Co(II) and ascorbate to discriminate bound Co from oxidized Co was developed. SG-1 spores were found to oxidize Co(II) over a wide range of pH, temperature, and Co(II) concentration. Leucoberbelin blue, a reagent that reacts with Mn(III,IV) oxides forming a blue color, was found to also react with Co(III) oxides and was used to verify the presence of oxidized Co in the absence of added Mn(II). Co(II) oxidation occurred optimally around pH 8 and between 55 and 65°C. SG-1 spores oxidized Co(II) at all Co(II) concentrations tested from the trace levels found in seawater to 100 mM. Co(II) oxidation was found to follow Michaelis-Menten kinetics. An Eadie-Hofstee plot of the data suggests that SG-1 spores have two oxidation systems, a high-affinity-low-rate system (K(m), 3.3 × 10(-8) M; V(max), 1.7 × 10(-15) M · spore(-1) · h(-1)) and a low-affinity-high-rate system (K(m), 5.2 × 10(-6) M; V(max), 8.9 × 10(-15) M · spore(-1) · h(-1)). SG-1 spores did not oxidize Co(II) in the absence of oxygen, also indicating that oxidation was not due to abiological Co(II) oxidation on the surface of preformed Mn(III,IV) oxides. These results suggest that some microorganisms may directly oxidize Co(II) and such biological activities may exert some control on the behavior of Co in nature. SG-1 spores may also have useful applications in metal removal, recovery, and immobilization processes.